Selection of proper input pattern in fuzzy logic algorithm for classifying the fault type in underground distribution system - Klomjit, Jittiphong; Ngaopitakkul, Atthapol (My University, 2017)
This paper present the proper input pattern of fuzzy logic algorithm for fault type classification in underground cable. The proposed algorithm using combination of discrete wavelet transform (DWT) and fuzzy logic. The DWT is applied to extract high frequency component from fault current waveform using mother wavelet daubechies4 (db4). The maximum coefficients detail of DWT and maximum ratio of DWT, obtained from phase A, B, C and zero sequence of fault current waveforms have been used as an input variables for decision algorithm. The obtained results in term of average accuracy have shown that the maximum ratio of DWT can achieved satisfactory accuracy in fault type classification.
Keywords: Fault Type; Fuzzy Logic; Underground Distribution System